Interactive Teaching Methods in Visual Arts Education: Enhancing Student Engagement and Creativity - Kamolova E’zoza Iskandar qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the role of interactive teaching methods in modern visual arts education and their impact on student engagement, creativity, and artistic literacy. Drawing on research by Shovdirov S. A., the study explores strategies such as group work, discussions, peer feedback, and collaborative digital projects. It emphasizes how these methods, combined with project-based learning and interdisciplinary approaches, create a dynamic, student-centered learning environment that fosters critical thinking, problem-solving, and innovative artistic expression.